Limite gravitacional pós-newtoniano da teoria TeVeS de Bekenstein - Juliana Diniz Bolzan de Oliveira (2007)
In this work the slow-motion, weak-field limit of Bekensteins TeVeS theory is studied through the parametrized post-newtoniam formalism, making possible its confrontation with experimental data, as well as the analysis of the specific limits in which the theory reduces to General Relativity and to the non-relativistic MOND model. The motivationand the development of ideas to support this theory, which is presented as an alternative to the assumption of the existence of Dark Matter, are also discussed.